Biological properties of novel polysuccinimide derivatives synthesized via quaternary ammonium grafting. (15th May 2020) - Velazco-de-la-Garza, Jaqueline; Avérous, Luc; Sosa-Santillán, Gerardo de Jesús; Pollet, Eric; Zugasti-Cruz, Alejandro; Sierra-Rivera, Crystel Aleyvick; Pérez-Aguilar, Nancy Verónica; Oyervides-Muñoz, Ernesto
Graphical abstract: Highlights: Two quaternary ammonium salts having a bromide end group were synthesized. Polysuccinimide derivatives were synthesized via quaternary ammonium grafting. The Chemical structures of the derivatives were supported by NMR and FTIR. Biological properties of the polysuccinimide derivatives were evaluated. Abstract: Two novel polysuccinimide (PSI) derivatives with antibacterial properties were synthesized by the reaction of polysuccinimide with different quaternary ammonium salts with an active terminal group. 4-bromobutyl-quinolinium bromide and 4-bromobutyl-benzalkonium bromide were synthesized from a quaternization reaction between 1, 4-dibromobutane and a tertiary amine (quinoline and N, N-dimethylbenzylamine). These ammonium salts with a bromide end group were chemically grafted along the polysuccinimide chains by quaternization of the nitrogen atoms of PSI. The chemical structures of these PSI derivatives were characterized by 1 H NMR analysis and FT-IR spectra. Thermal stability of these macromolecules was studied by thermo-gravimetric analysis. Antibacterial activity against E. coli strains was determined by the minimum inhibitory concentration and the minimum bactericidal concentration. In all the cases, it was possible to grant antibacterial properties to the polysuccinimide derivatives. Finally, hemolysis and 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assays were performed. PSI derivatives caused a lightly hemolytic effects on isolated human erythrocytes and murine fibroblast cell line, decreasing the cell proliferation of cancer cervical and breast cell lines.